Elementary school students’ layers of understanding in solving literacy problems based on Sidoarjo context - Ayuningtyas, Ilfia Nur; Amir, Mohammad Faizal; Wardana, Mahardika Darmawan Kusuma (IKIP Siliwangi and I-MES, 2024)
Elementary school students' difficulties in solving literacy problems are caused by students' lack of understanding of mathematical concepts. Using a specific regional context in literacy problems is essential to analyze layers of understanding elementary school more deeply. Based on Pirie-Kieren's theory, the study aims to analyze layers of understanding elementary school students in solving literacy problems in the context of Sidoarjo. The theory consists of eight understanding layers: primitive knowing, image making, image having, property noticing, formalising, observing, structuring, and inventing. A qualitative approach with a case study type was used as the research method. The research participants were 26 fifth-grade elementary school students. The determination of the research subjects was done by purposive technique. In this, the emphasis of determining the subject is taken on three categories of understanding by having one student each in the low, medium, and high categories. The results show that the layers of understanding of elementary school students are at the highest, namely observing. In addition, literacy problems in Sidoarjo contexts can overstimulate students' understanding. The context of learning should be used in Sidoarjo. Future research recommendations suggested using the regional context as a background for literacy problems in learning or problem-solving; this is needed to explore and develop layers of understanding to a higher level.